Thermogravimetric and mass-spectrometric analyses of combustion of spent potlining under N2/O2 and CO2/O2 atmospheres. (15th March 2019) - Sun, Guang; Zhang, Gang; Liu, Jingyong; Xie, Wuming; Kuo, Jiahong; Lu, Xingwen; Buyukada, Musa; Evrendilek, Fatih; Sun, Shuiyu
Highlights: Combustion behavior of spent potlining was explored in CO2 /O2 and N2 /O2 atmospheres. One-step thermal decomposition of spent potlining occurred between 450 and 800 °C. Burnout performance of char was improved by higher CO2 oxy-fuel atmosphere. Mean lowest activation energy occurred in 70% CO2 /30% O2 atmosphere. Abstract: Thermal decomposition and gaseous evolution of the spent potlining (SPL) combustion were quantified using thermogravimetric and mass-spectrometric analyses in CO2 /O2 and N2 /O2 atmospheres using three heating rates (15, 20 and 25 °C/min). The thermal decomposition of SPL occurred mainly between 450 and 800 °C. Based on the four kinetic methods of Friedman, Starink, Kissinger-Akahira-Sunose and Flynn-Wall-Ozawa under the various conversion degrees ( α ) from 0.1 to 0.7, the lowest apparent activation energy was estimated at 149.81 kJ/mol in the 70% CO2 /30% O2 atmosphere. The pre-exponential factor, and changes in entropy, enthalpy and free Gibbs energy were also estimated. The reaction model did not suggest a single reaction of the SPL combustion. With the α value of 0.25–0.7, the following function best described the reaction based on the Malek method: f ( α ) = 1/2 α and G ( α ) = ln α 2 . The gases released during the combustion process included CO2, CO, NOx, HCN, and HF.